2015
DOI: 10.4236/fmar.2015.31002
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assessment of the Morphology of the Piriform Aperture as an Indicator of Race

Abstract: Piriform apertures from skulls in the Bass Collection at the University of Tennessee were examined. The morphology of the perform aperture from digital images was captured using Adobe Measuring Tool 9.0 and data analyzed with SPSS 17.0. Twenty-four linear measurements from a central point of the aperture as well as the perimeter were evaluated to quantify a difference between Black and White populations. The statistical analyses employed Discriminate Functional Analysis followed by Stepwise analysis. Discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is reported that people who live in cold weather and dry climate tend to have narrower nose while people who live in warmer climate tend to have broader nose [6,9]. Therefore Europeans tend to have a narrower triangular nasal opening while Africans tend to have a much wider and more rectangular opening [4,10]. This assertion is logical because it is known that the moistening and heating of the inspired air are better with a narrow piriform aperture [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is reported that people who live in cold weather and dry climate tend to have narrower nose while people who live in warmer climate tend to have broader nose [6,9]. Therefore Europeans tend to have a narrower triangular nasal opening while Africans tend to have a much wider and more rectangular opening [4,10]. This assertion is logical because it is known that the moistening and heating of the inspired air are better with a narrow piriform aperture [3].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the proportions of the nose vary between ethnic groups, the size and shape of the nose do not actually confer specificity of race such as Caucassian, Asian or African [4]. But nasal index exhibit sexual dimorphism [4] and therefore it is a useful tool in forensic science.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations